With a little help from my friends: adopting a P-E fit perspective in understanding the value of organizational learning climate for sustainable employability - Vuuren, Tinka Van; Van der Heijden, Beatrice I. J. M.; Semeijn, Judith H. (Frontiers in Psychology, 2023)
Purpose: The objective of this study was to investigate how organisational learning climate (measured as developmental opportunities and team support for learning), career commitment, and age are related to employees’ self-perceived employability, vitality and work ability (e.g., their sustainable employability). This study adopted a P-E fit perspective building upon the notion that sustainable employability is a function of both the person (P) and the environment (E) and tests a three-way interaction between organisational learning climate, career commitment, and age. Design: 211 members of the support staff of a Dutch university completed a survey. Hierarchical stepwise regression analysis was used to analyse the data. Findings: Only one of the two dimensions of organisational learning climate that we measured, namely the developmental opportunities, appeared to be associated with all indicators of sustainable employability. Career commitment only had a direct positive relationship with vitality. Age was negatively related to self-perceived employability and to work ability, but not to vitality. The relationship between developmental opportunities and vitality was negatively influenced by career commitment (a negative two-way interaction effect), while a positive three-way interaction effect was found between career commitment, age, and development opportunities, and with self-perceived employability as the outcome. Theoretical and practical implications: Our findings confirmed the relevance of adopting a P-E fit perspective on sustainable employability, and of considering the possible role of age in this. It requires more detailed analyses in future research to unravel the role of age in the shared responsibility for sustainable employability. In practice, the results of this study imply that organisations should provide all employees with a working context that facilitates learning, however with a special focus on older employees, for whom it is a particular challenge to protect their sustainable employability, possibly due to age-related stereotyping. Originality: This study adopted a P-E fit perspective on sustainable employability and examined the association between organisational learning climate and all three components of sustainable employability: self-perceived employability, vitality and work ability. Moreover, it investigated whether and how the employee’s career commitment and age influence this relationship.